2020
DOI: 10.3390/ijms21144970
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Induces Melanogenesis in Human SK-MEL-1 Melanoma Cells Involving Glycogen Synthase Kinase-3 and Reactive Oxygen Species

Abstract: Melatonin is present in all living organisms where it displays a diversity of physiological functions. Attenuation of melanogenesis by melatonin has been reported in some mammals and also in rodent melanoma cells. However, melatonin may also stimulate melanogenesis in human melanoma cells through mechanisms that have not yet been revealed. Using the human melanoma cells SK-MEL-1 as a model, an increase in both tyrosinase activity and melanin was already observed at 24 h after melatonin treatment with maximal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Glutathione tripeptide plays a critical role in antioxidant defense, thiol status maintenance, and xenobiotic detoxification [ 44 ]. Previous studies showed that both N-acetyl L-cysteine and glutathione at 5 mM attenuated melatonin-induced melanogenesis in human SK-MEL-1 melanoma cells [ 45 ]. Glutathione, glutathione monoethyl ester, and glutathione disulfide whitened the skin to varying degrees [ 27 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione tripeptide plays a critical role in antioxidant defense, thiol status maintenance, and xenobiotic detoxification [ 44 ]. Previous studies showed that both N-acetyl L-cysteine and glutathione at 5 mM attenuated melatonin-induced melanogenesis in human SK-MEL-1 melanoma cells [ 45 ]. Glutathione, glutathione monoethyl ester, and glutathione disulfide whitened the skin to varying degrees [ 27 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, previously reported observations have shown the ability of iron to induce cellular oxidative stress through multiple iron-dependent ROS activation mechanisms: apoptosis and necroptosis [ 69 , 70 ], ferroptosis [ 71 ], or pyroptosis [ 72 ]. The increased ROS levels in melanoma cells stimulate melanogenesis [ 73 , 74 , 75 ], an important process that can protect melanoma cells, especially through the free radical scavenging properties [ 49 , 50 , 51 ] and Fe (II) [ 76 ] or Fe (III) [ 77 ] chelating abilities of melanin. Moreover, the ability of melanin to bind Fe (III) ions could be involved in the similar perimembranous arrangement of the SaIONs and melanin deposits, highlighted by microscopy in the Perl Prussian blue-stained samples from the ITO1w group ( Figure 4 h).…”
Section: Discussionmentioning
confidence: 99%
“…There are reports that melatonin derived from 5-HT induces or inhibits melanogenesis [ 179 , 180 , 181 , 182 ]. This difference seems to be due to the difference in the concentration of melatonin used and the cell line.…”
Section: Amines Neurotransmitters and Their Receptors In Skin Pigmentation Diseasesmentioning
confidence: 99%